Zirconium behaviour during electrorefining of actinide-zirconium alloy in molten LiCl-KCl on aluminium cathodes - Meier, Ralph; Souček, P.; Malmbeck, R.; Krachler, M.; Rodrigues, A.; Claux, B.; Glatz, J. -P.; Fanghänel, Thomas (Journal of nuclear materials, 2016)
A pyrochemical electrorefining process for the recovery of actinides from metallic nuclear fuel based on actinide-zirconium alloys (An-Zr) in a molten salt is being investigated. In this process actinides are group-selectively recovered on solid aluminium cathodes as An-Al alloys using a LiCl-KCl eutectic melt at a temperature of 450 °C. In the present study the electrochemical behaviour of zirconium during electrorefining was investigated. The maximum amount of actinides that can be oxidised without anodic co-dissolution of zirconium was determined at a selected constant cathodic current density. The experiment consisted of three steps to assess the different stages of the electrorefining process, each of which employing a fresh aluminium cathode. The results indicate that almost a complete dissolution of the actinides without co-dissolution of zirconium is possible under the applied experimental conditions.
Gesehen am 06.05.2020